Sintesis Soluble Polianilin dengan Variasi Jenis dan Konsentrasi Dopan - Retno Fitri Wulandari; Nugrahani primary putri (Jurnal Teori dan Aplikasi Fisika, 2021)
This study reports the synthesis of soluble polyaniline by the oxidation polymerization method with various dopants HCl, H2SO4, and Fumaric acid (FA). This dopant variation is carried out to obtain polyaniline with optimum solubility and electrical conductivity. The results of FTIR characterization showed several characteristic polyaniline bonds from the samples that had been synthesized. PANi/FA with a concentration of 1M has the best solubility compared to PANi/HCl and PANi/H2SO4, with a solubility value of 5.7% in NMP solvents. The electrical conductivity of all samples was measured by the two-point probe method. PANi / HCl with a concentration of 1M has the best conductivity than PANi/FA and PANi/H2SO4 with a value of 48 x10-4 S/cm. The morphology of the oxidized polyaniline powder was observed using SEM. SEM results showed the morphology of polyaniline in the form of an interconnected sponge.